83 - RENAL FUNCTION DURING MAXIMAL PHYSICAL EXERCISE IN APPARENTLY HEALTHY ELDERLY PEOPLE (Fiep Bulletin - online, 2023)
Actually, physical education must include human beings of different ages, especially the elderly. Adequate guidance in the practice of physical activity will improve your quality of life. However, there are conditions such as exercise-induced proteinuria, which in the long term can lead to kidney disease if the duration and intensity of exercise are not properly considered. Therefore, the purpose of the study was to determine the effect of different intensities of physical exercise on proterinuria (albuminuria) in adults apparently healthy older adult. The present study is of an experimental, prospective, longitudinal and comparative nature in men over 65 years of age without manifestations of disease and participated in recreational activities. Participated 25 older people with mean age of 72 + 9.3, and without pathology. They They performed 3 treadmill exercise tests: maximal and submaximal physical exercise for 30 minutes at 60 and 80% of the observed heart rate. The order of tests was randomized. The participants presented a slight presence of microalbuminuria, which reverted 24 hours after their exercise. Guiding the practitioner of physical activity will allow a better state of health and avoid kidney damage.
Keywords: Physical activity; aging; microalbuminuria; exercise intensity